2015
DOI: 10.13057/psnmbi/m010814
|View full text |Cite
|
Sign up to set email alerts
|

Review: Tumbuhan di kota urban Indonesia: Nilai bioteknologis dan proyeksi keragaman pada 2050

Abstract: Abstrak. Kemal RA, Yulita A, Nufadianti G, Rosadi I, Muthmainah SI. 2015. Tumbuhan di kota urban Indonesia: Nilai bioteknologis dan proyeksi keragaman pada 2050. Pros Sem Nas Masy Biodiv Indon 1: 1836-1841.Biodiversitas di kota urban perlu dipelajari dan dilestarikan. Sumber keragaman tumbuhan di kota urban di antaranya adalah Ruang Terbuka Hijau. Studi literatur menunjukkan beberapa spesies yang ditemukan di kota Jakarta memiliki nilai bioteknologis. Biji Cerbera manghas, salah satu spesies yang paling umum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Finally, planting FTS stimulates economic activity in a particular community. For example, in Jakarta, some people utilize tree species with medicinal effects; these are planted along the roadside and include velvet tamarinds (Digallium indum), jackfruits, and coconuts [133]. In the present study, Averrhoa bilimbi was found to be a favorite tree among people living in coastal cities, such as Makassar, Jakarta Utara, Banjarmasin, Jayapura, and Kupang, because the A. bilimbi fruit is a useful herb for removing fishy smells in cooking.…”
Section: Fts and City Servicesmentioning
confidence: 68%
“…Finally, planting FTS stimulates economic activity in a particular community. For example, in Jakarta, some people utilize tree species with medicinal effects; these are planted along the roadside and include velvet tamarinds (Digallium indum), jackfruits, and coconuts [133]. In the present study, Averrhoa bilimbi was found to be a favorite tree among people living in coastal cities, such as Makassar, Jakarta Utara, Banjarmasin, Jayapura, and Kupang, because the A. bilimbi fruit is a useful herb for removing fishy smells in cooking.…”
Section: Fts and City Servicesmentioning
confidence: 68%